Investigating the Social Drivers of “Duta Kayuagung”: A Crime Culture in Kayuagung, South Sumatra - Regina, Rani; Noviza, Neni; Fitri, Hartika Utami (Grief and Trauma, 2024)
The aim of this research is to identify the factors contributing to the occurrence of Duta crimes in Kayuagung, OKI, and to explore the social motives of the perpetrators. This study uses a field research approach with a qualitative, descriptive methodology. Data collection techniques included observation, interviews, and documentation. The subjects of this research were four individuals. The findings indicate that the main social motives driving Duta crimes in Kayuagung include economic pressures, social environmental influences, and the pursuit of social status, such as assisting the local community or contributing to the construction of mosques, prayer rooms, and roads. Economic hardships often compel individuals to seek quick ways of making money, while influences from the social environment, such as peer groups and family, significantly shape criminal behavior. Additionally, the desire for social status and recognition within the community serves as a key motivator. This research underscores the need for comprehensive social interventions, including economic empowerment, education, and the reinforcement of social values, to help reduce crime in society.